1995
DOI: 10.3406/ahess.1995.279349
|View full text |Cite
|
Sign up to set email alerts
|

Du Nylon et des Bombes du Pont de Nemours, l'Etat américain et le nucléaire, 1930-1960

Abstract: En 1952, David Lilienthal, ancien directeur de la Tennessee Valley Authority et de l'Atomic Energy Commission, publiait Big Business, essai dans lequel il faisait l'apologie des grandes entreprises en affirmant qu'elles composaient désormais l'une des figures irrévocables de la modernité, caractérisée selon lui par des besoins de consommation toujours croissants qu'elles seules étaient capables de satisfaire. La société d'abondance était perçue par Lilienthal, à l'instar de l'historien David Potter, l'auteur d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 7 publications
2
5
0
Order By: Relevance
“…If scrambling was active, a mixture of NiL 3 Ni and VOL 3 VO complexes in a 1/1 ratio would be present. The magnetic data corresponding to such a mixture could agree with the data of the genuine NiL 3 VO complex, as we demonstrate that the magnetic interaction in the dinuclear VOL 3 VO complex is very weak and that de dinuclear NiL 3 Ni complex is diamagnetic. On the contrary, the EPR data become informative.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…If scrambling was active, a mixture of NiL 3 Ni and VOL 3 VO complexes in a 1/1 ratio would be present. The magnetic data corresponding to such a mixture could agree with the data of the genuine NiL 3 VO complex, as we demonstrate that the magnetic interaction in the dinuclear VOL 3 VO complex is very weak and that de dinuclear NiL 3 Ni complex is diamagnetic. On the contrary, the EPR data become informative.…”
Section: Discussionsupporting
confidence: 77%
“…So we again show that a symmetrical ligand possessing two identical N2O2 coordination sites allows formation of heterodinuclear complexes, what is quite surprising and original. We have previously shown that the free L 3 H4 ligand reacts with vanadyl ions in basic medium to yield the VOL 3 VO complex [5]. We have also demonstrated that the thermal dependence of the magnetic susceptibility follows a Curie law, with C = 0.69 cm 3 mol -1 K, so that the magnetic interaction of the two vanadyl ions is absent or very weak.…”
Section: Scheme 2 Schematic Representation Of Genuine Ligands and Com...mentioning
confidence: 81%
See 3 more Smart Citations